Peran Motor Listrik pada Transportasi Ramah Lingkungan - Slamet Riyadi (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2018)
The fossil based fuel crisis and environmental degradation issues have caused the transportation system to use electric motors as an alternative to combustion engines. The emergence of electric hybrid vehicles and electric vehicles has been a sign that the revolution in the field of transportation has reached the implementation stage. DC motors that are capable to generate large torque becomes an option at first, but due to its limitations then other types of motors which have advantages such as DC motor but eliminating the its weakness are developed. BLDC (Brushless Direct Current) motors and switched reluctance motors are priority in implementation. This paper describes the characteristics and performance of the three motors which can be used as the background for developing environmentally friendly transportation system